ENGENHEIROS PROFESSORES: UMA PRIMEIRA APROXIMAÇÃO DE SUAS CONCEPÇÕES SOBRE OS SABERES DOCENTES - Hidalga, Wanderlei Aguilera (2006)
This study which fits the professor engineer in engineering courses academic knowledge research context, has had some questioning as a reference guide: Is there some basic knowledge to be considered in the engineering professor s education? Would the experience knowledge have a relevance on other types of knowledge? Which types of knowledge are mobilized by engineers in their academic performance? Schulman (1986), Tardif (2002), and Saviani (1996), among others, offered the theoretical references for the study project. For the empirical research, interviews with five engineering professors were done, proceeding to content analysis. In the depth of the analysis, two engineering professors narratives were considered: from the author and from one of the interviewed professors, who accepted to do an intensive interview. The results bring a problem chart from the engineering professors lived experiences, revealing an academic knowledge emphasis which, in practice, articulate together the experience, curriculum-didatics, attitude and contextually critical knowledge showing that the academic in engineering courses is still strongly influenced by the dominant epistemology from modern science. The academic, in engineering courses, supports an academic conception as gift, relegating the pedagogical knowledge to a plan B.